2017
DOI: 10.1016/j.physb.2016.10.014
|View full text |Cite
|
Sign up to set email alerts
|

μSR study of stoichiometric NbFe2

Abstract: The magnetic ground state of nominally stoichiometric single crystalline NbFe 2 is investigated by bulk magnetisation and muon spin relaxation techniques. Magnetic order clearly emerges below the critical temperature T N =10.3 K and is dominated by randomly orientated quasi-static moments. The local field distribution observed by muons can be explained by the phenomenological Gaussian-broadened-Gaussian Kubo Toyabe relaxation function. The observed short range order could be used to describe a new magnetic gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…Conversely, in a paramagnetic phase at both muon sites there will be essentially the same field and field distribution, and the assumption of a single muon stopping will be sufficient to fit the experimental data (the site occupation in the SDW phase will be discussed in the following subsection). This conclusion is in full accordance with the fit procedures used in previous µSR studies on Nb 1−y Fe 2+y 19,20 .…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…Conversely, in a paramagnetic phase at both muon sites there will be essentially the same field and field distribution, and the assumption of a single muon stopping will be sufficient to fit the experimental data (the site occupation in the SDW phase will be discussed in the following subsection). This conclusion is in full accordance with the fit procedures used in previous µSR studies on Nb 1−y Fe 2+y 19,20 .…”
Section: Methodssupporting
confidence: 91%
“…By now, these findings have been validated by a multitude of experimental techniques including microscopic probes such as muon spin relaxation and elastic neutron scattering. [19][20][21] . It was concluded, that the ferromagnetic phases have a magnetic moment below 0.1 µ B /Fe atom 17,19,21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic phases of Nb 1−y Fe 2+y at low temperatures exhibit a strong sensitivity on the actual sample composition, resulting in a complex magnetic phase diagram [13][14][15][16]. Extensive investigations in recent years using different measurement techniques have established that Nb 1−y Fe 2+y can be pushed into a quantum critical point (QCP) by variation of y [16][17][18][19][20][21][22], with the phase diagram depicted in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…By now, these findings have been validated by a multitude of experimental techniques including microscopic probes such as muon spin relaxation and elastic neutron scattering. [19][20][21]. It was concluded that the ferromagnetic phases have a magnetic moment below 0.1 μ B /Fe atom [17,19,21].…”
Section: Introductionmentioning
confidence: 99%